Prediction of unfavorable outcomes in cryptococcal meningitis: results of the multicenter infectious Diseases International Research Initiative (ID-IRI) cryptococcal meningitis study (vol 37, pg 1231, 2018) - (:unkn) unknown (SPRINGER, 2018)
In the original version of this article, Mustafa Sunbul was not included in the list of authors for this article. The name has been added accordingly.